A CRISPR/Cas9 knockout model for AADC deficiency reveals structural loop3 instability as a key driver of catalytic failure - Uçar, Sema Kalkan; Yıldırım, Cem; Opladen, Thomas (The FEBS journal, 2025)
The CRISPR-Cas9 dopa decarboxylase (DDC) gene knockout SH-SY5Y model for aromatic L-amino acid decarboxylase (AADC) deficiency provides a valuable neuronal platform for functional and structural investigation of pathogenic variants. In their study, Bertoldi et al. successfully recapitulate the biochemical and metabolic hallmarks of AADC deficiency using the AADC catalytic variants R347Q and L353P. Their combined structural and cellular approach identifies loop3 dynamics as a critical determinant of enzymatic dysfunction. This model may pave the way for the development of precision therapies.
Online verfügbar: 24. Juli 2025
Gesehen am 09.12.2025